Utilization of Waste Material for Stabilization of Lateritic Soil - Chaiyaput, Salisa; Ayawanna, Jiratchaya; Manandhar, Suman; Sae-Ueng, Songklod (My University, 2024)
The waste materials from the manufacturing process were employed for the purpose of enhancing the strength of lateritic soil grade E, which exhibited the least suitable mechanical properties. The present study focused on the investigation of waste materials from the steel manufacturing process, namely electric arc furnace (EAF) slag and ladle furnace (LF) slag, as well as waste material from asphalt concrete plants, specifically asphalt waste dust (AWD). These waste materials were examined in relation to their potential utilization in combination with lateritic soil. The mixing ratio employed in this investigation was 10% by weight (wt%). A mixture of 5 wt% ordinary Portland cement was mixed with 90 wt% lateritic soil and 10 wt% asphalt waste dust to enhance the efficiency of lateritic soil stabilization. The efficiency of waste materials was evaluated by the California bearing ratio (CBR) test. The integration of EAF slag and LF slag, byproducts of the steel manufacturing process, significantly improved the CBR more than 5 times and 7 times, respectively, for EAF and LF mixes compared to natural lateritic soil. Furthermore, the CBR of lateritic soil blended with asphalt waste dust and Portland cement exhibited approximately 20 times higher than that of natural lateritic soil and cement-stabilized lateritic soil.
Keywords: Asphalt dust; Electric arc furnace slag; Ladle furnace slag; Soil stabilization